2020
DOI: 10.3390/polym12010212
|View full text |Cite
|
Sign up to set email alerts
|

Core-Shell Graphitic Carbon Nitride/Zinc Phytate as a Novel Efficient Flame Retardant for Fire Safety and Smoke Suppression in Epoxy Resin

Abstract: Novel core-shell graphitic carbon nitride/zinc phytate (g-C3N4/PAZn) flame retardant was simple synthetized using two-dimensional g-C3N4 and bio-based PAZn by self-assembly and incorporated into epoxy resin (EP) for improving the fire safety. The flame retardance and smoke suppression were investigated by cone calorimetry. The results indicated that g-C3N4/PAZn-EP displayed outstanding flame retardancy and smoke suppression, for example, the peak heat release rate and peak smoke production rate decreased by 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The TSP curves demonstrated that, after the flame retardant coating, the TSP value greatly decreased from 10.99 m 2 for neat EPS to 0.457, 0.196, 0.394, and 0.133 m 2 for EPS/IFR1, EPS/IFR2, EPS/IFR3, and EPS/MDI/IFR3, respectively as shown in Figure 5 d and Table 3 . The substantial reduction in TSP demonstrated that the water-based intumescent flame retardant coatings effectively suppressed smoke formation, which would remarkably increase the chances of people escaping in a fire [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TSP curves demonstrated that, after the flame retardant coating, the TSP value greatly decreased from 10.99 m 2 for neat EPS to 0.457, 0.196, 0.394, and 0.133 m 2 for EPS/IFR1, EPS/IFR2, EPS/IFR3, and EPS/MDI/IFR3, respectively as shown in Figure 5 d and Table 3 . The substantial reduction in TSP demonstrated that the water-based intumescent flame retardant coatings effectively suppressed smoke formation, which would remarkably increase the chances of people escaping in a fire [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…A lot of research works have been carried out, and the direct addition of flame retardants has the advantages of convenience and economy, thus becoming the most chosen approach. Halogen flame retardant has advantages of high flame retardant efficiency [ 16 ], low dosage and good compatibility with materials, however, a large amount of smoke and poisonous and corrosive gases, such as dioxins, will be produced during combustion, causing great harm to the environment. Moreover, metal hydroxide is also an available flame retardant synergist, which is non-toxic and has good stability, while plenty of additive amounts and poor flowability will reduce the mechanical properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the ablation process, a protective layer is formed in advance to protect the substrate, thereby enhancing the compactness of the substrate. Aluminum hypophosphite (AHP), another type of flame retardant, 35–39 is conducive to form ceramic layer, which may play a role to strengthen char layer 41–46 . Thus, the influence of ZB on the ablative properties of epoxy‐modified silicon rubber and a comparison with AHP‐ and ZB/AHP‐containing counterparts were systematically studied.…”
Section: Introductionmentioning
confidence: 99%